Medical ethics / Laura K Egendorf - Egendorf, Laura K.
Doctors and other health care professionals have long grappled with the morality of certain controversial medical procedures. Chapters in this volume include a debate on the fairness of the health care system and examinations of the ethics of organ transplants, reproductive technologies, and genetic technologies.